Time trends in dietary fat intake in a sample of German children and adolescents between 2000 and 2010: not quantity, but quality is the issue. Issue 1 (14th January 2014) - Libuda, Lars; Alexy, Ute; Kersting, Mathilde
<x content-type="archive" xml:space="preserve">Abstract</x> Dietary fat intake in childhood may influence the risk for developing chronic diseases. The objective of the present study was to examine secular trends in the parameters of fat intake between 2000 and 2010 in a sample of German children and adolescents (n 808) participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study. Dietary data from 4380 3 d weighed dietary records were analysed using repeated-measures regression to determine time trends in fat quantity, i.e. the intake of total fat, and in fat quality, i.e. the ratios of SFA, MUFA and PUFA. In young children (2–3 years) and in adolescents (13–18 years), total fat intake remained stable over time, but decreased by 0·08 % of total energy (%E) per year in 4–12-year-old children. In 2010, median fat intake was at the upper end of the recommendations. SFA intake decreased slightly in 2–3- and 4–12-year-old children by 0·09 and 0·05 %E per year, respectively. MUFA and PUFA intakes remained stable in all the age groups except in adolescents. Here, PUFA intake decreased initially, but increased between 2005 and 2010. In 2010, only between 3 and 18 % of the respective age groups had an intake of SFA or PUFA within the recommendations. In conclusion, fat quantity and quality did not change substantially between 2000 and 2010. Fat quality, in particular, needs to be improved, since a large percentage of our sample did not meet the recommended intakes for SFA and PUFA.